Voluntary disclosures by activist investors: the role of activist expectations* - McDonough, Ryan; Nagar, Venky; Schoenfeld, Jordan (Review of Accounting Studies, 2024)
Abstract Activist investors in a firm often voluntarily release information about their governance intentions to the public. Voluntary disclosure theory suggests that an activist investor will disclose when she expects other investors to respond positively and support her in upcoming corporate control contests. We find that activists’ disclosures are accompanied by positive abnormal returns, reductions in bid-ask spreads, and increases in future earnings relative to similar targets without voluntary activist disclosures. Disclosures by activists who demand a board seat (the most common demand) have the highest announcement returns, and disclosers also win proxy contests and directorships more frequently than non-disclosers. These findings suggest that the activist’s beliefs about investor response in both pricing and voting are an important driver of her disclosure choice.